ẢNH HƯỞNG CỦA CHẾ PHẨM VI KHUẨN LACTIC LÊN SỰ THAY ĐỔI HÀM LƯỢNG AXIT AMIN CỦA CÁ TẠP SAU THỜI GIAN BẢO QUẢN VÀ ỨNG DỤNG CHO NUÔI TRỒNG THỦY SẢN - Trang, Nguyễn Thế; Mấn, Trần Đình; Hà, Phạm Thanh (Vietnam Journal of Science and Technology, 2012)
THE CHANGE OF AMINO ACID AFTER FERMENTATION OF FISH SILAGE USING LACTIC ACID BACTERIA COMPOST AND APPLICATION IN AQUACULTURE Lactic acid fermentation is utilized throughout the world as a prime method of preserving fresh food. Fish, however, is more perishable than other meats as it contains relatively large quantities of free amino acids. If fish is not preserved, it will quickly spoil. The lactic acid bacteria (LAB) are added to raw fish due to the formation of lactic acid. In these products, the pH of fish mixture is lowered making the product safer and easier to keep. The suitability of LAB for fish silage fermentation was investigated. Four kinds of compost were the respectively prepared, using without LAB; with two of LAB strains; with the other two of LAB strains and with four of LAB strains as fermentation starter. The starter were added to raw fish and stored at room temperature for 25 days. Changes in amino acids of silage after storage were evaluated, and the values were compared to the frozen fish. There were no specific changes in the level of amino acid within 25 days of the storage. Total amino acids for frozen fish and for fermented silages were added with LAB strains were 3.90 and 3.23% - 3.43% (g amino acid/ 100 g sample), respectively. Total free amino acids were 52.03 and 58.11% - 61.40% (g amino acid/ 100 g sample), respectively. Fermented fish silage can be successfully prepared using fermentation starters of complex of four of LAB strains P. pentosaceus HN02; L. brevis HN26; L. lactis subsp. lactis HN11 and L. delbrueckii subsp. delbrueckii HN34 within 25 days of storage.